Bioabsorbable Versus Titanium Screws in Anterior Cruciate Ligament Reconstruction Using Hamstring Autograft: A Prospective, Randomized Controlled Trial With 13-Year Follow-up. Issue 6 (May 2020) - Sundaraj, Keran; Salmon, Lucy J.; Heath, Emma L.; Winalski, Carl S.; Colak, Ceylan; Vasanji, Amit; Roe, Justin P.; Pinczewski, Leo A.
Background: Bioabsorbable screws for anterior cruciate ligament reconstruction (ACLR) have been a popular choice, with theoretical advantages in imaging and surgery. Titanium and poly-L-lactic acid with hydroxyapatite (PLLA-HA) screws have been compared, but with less than a decade of follow-up. Purpose/Hypothesis: The purpose was to compare long-term outcomes of hamstring autograft ACLR using either PLLA-HA screws or titanium screws. We hypothesized there would be no difference at 13 years in clinical scores or tunnel widening between PLLA-HA and titanium screw types, along with high-grade resorption and ossification of PLLA-HA screws. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Forty patients undergoing ACLR were randomized to receive either a PLLA-HA screw or a titanium screw for ACL hamstring autograft fixation. Blinded evaluation was performed at 2, 5, and 13 years using the International Knee Documentation Committee score, Lysholm knee score, and KT-1000 arthrometer. Magnetic resonance imaging (MRI) was performed at 2 or 5 years and 13 years to evaluate tunnel volumes, ossification around the screw, graft integration, and cyst formation. Computed tomography (CT) of patients with PLLA-HA was performed at 13 years to evaluate tunnel volumes and intratunnel ossification. Results: No differences were seen in clinical outcomes at 2, 5, or 13 years between the 2 groups. At 13 years, tibial tunnel volumes were smaller for the PLLA-HA group (2.17 cm 3 ) compared with the titanium group (3.33 cm 3 ; P = .004). By 13 years, the PLLA-HA group had complete or nearly complete resorption on MRI or CT scan. Conclusion: Equivalent clinical results were found between PLLA-HA and titanium groups at 2, 5, and 13 years. Although PLLA-HA screws had complete or nearly complete resorption by 13 years, tunnel volumes remained largely unchanged, with minimal ossification.